2013
DOI: 10.1159/000358798
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HLA Diversity on Donor Selection in Organ and Stem Cell Transplantation

Abstract: The human major histocompatibility complex is a multigene system encoding polymorphic human leucocyte antigens (HLA) that present peptides derived from pathogens to the immune system. The high diversity of HLA alleles and haplotypes in the worldwide populations represents a major barrier to organ and allogeneic hematopoietic stem cell transplantation, because HLA incompatibilities are efficiently recognized by T and B lymphocytes. In organ transplantation, pre-transplant anti-HLA antibodies need to be taken in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 42 publications
(43 reference statements)
0
25
0
1
Order By: Relevance
“…The HLA gene complex is highly diverse, with more than 3,000 variant alleles discovered in the HLA-A, B, or C loci, to date, in human populations, and it can also form 15,000–70,000 possible α and β chain combinations for HLA-DQ, DR, and DP molecules (from the IMGT/HLA website: , September 13, 2016). This profound heterogeneity confers hypervariable interaction in antigen presentation for conventional T cell activation in human populations and is also functionally reflected in the difficulty of finding non-rejected graft donors for organ transplantation except for identical twins (99). …”
Section: Highly Conserved Antigen-presenting Moleculesmentioning
confidence: 99%
“…The HLA gene complex is highly diverse, with more than 3,000 variant alleles discovered in the HLA-A, B, or C loci, to date, in human populations, and it can also form 15,000–70,000 possible α and β chain combinations for HLA-DQ, DR, and DP molecules (from the IMGT/HLA website: , September 13, 2016). This profound heterogeneity confers hypervariable interaction in antigen presentation for conventional T cell activation in human populations and is also functionally reflected in the difficulty of finding non-rejected graft donors for organ transplantation except for identical twins (99). …”
Section: Highly Conserved Antigen-presenting Moleculesmentioning
confidence: 99%
“…The search for compatible donors in bone marrow transplantation is a main health issue, and the impact of diversity deserves special attention . The observation of substantial HLA genetic variation at the regional level in Europe and surrounding areas indicates that some allelic combinations, including rare phenotypes, may not be found with a similar probability in all these populations.…”
Section: Implication For Studies In Anthropology Transplantation Andmentioning
confidence: 99%
“…HLA genes are highly polymorphic 1,2 and as such are involved in allogeneic immune responses following hematopoietic stem cell transplantation (HSCT), where they play an important role in graft-vs-host disease (GVHD). 3 Studies have shown that donor-recipient HLA mismatch is significantly associated with worse survival outcomes. [4][5][6][7] Around 35 000 units of umbilical cord blood (CB) have been transplanted worldwide since the first successful transplant in 1988.…”
Section: Introductionmentioning
confidence: 99%